Genetic diversity of babesia bovis studied longitudinally under natural transmission conditions in calves in the state of rio de janeiro, brazil - Matos, Carlos António [UNESP]; Silva, Jenevaldo Barbosa da [UNESP]; Gonçalves, Luiz Ricardo [UNESP]; Mendes, Natalia Serra [UNESP]; Alvarez, Dasiel Obregón; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (FapUNIFESP (SciELO), 2020)
Serum and DNA samples from 15 naturally infected calves in Seropédica, Brazil, were obtained quarterly from birth to 12 months of age, in order to longitudinally evaluate their humoral immune response against Babesia bovis and the merozoite surface antigen diversity of B. bovis. Anti-B. bovis IgG antibodies were detected by an indirect fluorescent antibody test (IFAT) and enzyme-linked immunosorbent assay (ELISA). Using DNA amplification, sequencing and phylogenetic analysis, the genetic diversity of B. bovis was assessed based on the genes that encode merozoite surface antigens (MSA-1, MSA-2b and MSA-2c). The serological results demonstrated that up to six months of age, all the calves developed active immunity against B. bovis. Among the 75 DNA samples evaluated, 0, 3 and 5 sequences of the msa-1, msa-2b and msa-2c genes were obtained, respectively. The present study demonstrated that the msa-2b and msa-2c gene sequences amplified from blood DNA of B. bovis-positive calves were genetically diversified. These data emphasize the importance of conducting deeper studies on the genetic diversity of B. bovis in Brazil, in order to design diagnostic antigens and vaccines in the future.
Diversidade genética de babesia bovis estudada longitudinalmente em condições de transmissão natural entre bezerros no estado do rio de janeiro, brasil
Keywords: Babesia bovis; Bovine babesiosis; Genetic diversity; MSA; Serology